Adoption and Challenges of Zero-Carbon Energy among Rural Smallholder Farmers in Southeast Nigeria - Emmanuel Ejiofor Omeje (Journal of Agricultural Extension)
This study investigated the awareness, adoption, energy productivity and challenges of zero-carbon energy (ZCE) among rural smallholder farmers in southeast Nigeria. A Multistage sampling procedure was used to select 378 respondents. Data were analyzed using percentages, mean, ranking statistics, and a single-factor productivity model. Findings showed that the majority (97.4%) of the respondents were aware that ZCE could be used for farming activities, 15.0% knew about wind power, 6.0% were aware of hydropower, and 2.7% were not aware of any types of ZCE. Also, 90% of the farmers were aware of the major benefits of ZCE. Only 28.6% adopted the use of ZCE, while photovoltaic solar energy was the only type of ZCE adopted by the users. The major farming activities powered by ZCE, according to the adopters, were the lighting of the farmhouses (89.8%) and water supply (15.7%). The energy productivity of ZCE (4.1%) was higher than fossil fuel (1.8%). The high-ranking challenges of ZCE adoption among the farmers were the high installation cost (82.0%) and lack of credit/ subsidy for ZCE (77.0%). This study recommends that extension officers should do more to educate farmers to use the ZCE options since they have higher energy productivity than fossil fuels.